COMPARATIVE ANALYSIS OF CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON ASSETS, RETURN ON EQUITY, NET PROFIT MARGIN AND EARNING PER SHARE COMPANY BEFORE AND AFTER ACQUISITION ON LISTING COMPANY IN INDONESIA STOCK EXCHANGE - DEMPO, BUNGA MASITHA (Jurnal Ilmiah Mahasiswa FEB, 2018)
The  purpose  of  this  research  is  to  know  the  difference  of  acquirer's  financial performance as measured by Current Ratio, Debt To Equity Ratio, Return On Asset, Return On Equity, Net Profit Margin and Earning Per Share between before and after acquisition. The  type  of  research  used  in  the  study  is  comparative,  with  the  population  used  are companies  listing  on  the  Indonesia  Stock  Exchange  between  2006-2016.  The  sampling technique used purposive sampling method, so that got the sample of 5 companies doing the acquisition activity in 2011 period in Indonesia Stock Exchange. Data analysis methods used to answer the hypothesis using Paired Sample t-test and Wilcoxon Signed Rank Test.      Based on the results of the analysis with paired sample t-test all financial ratios did not show any difference between before and after the acquisition. In addition, the Wilcoxon Signed Rank Test test results explain that the ratio of CR, DER, ROA, and ROE also shows no significant difference between before and after the company made the acquisition.Keywords: Financial Performance, Financial Ratios, and Acquisitions